Therapy with low-dose azacitidine for MDS in children and young adults: a retrospective analysis of the EWOG-MDS study group - Cseh, Anna-Maria; Niemeyer, Charlotte; Yoshimi-Nöllke, Ayami; Catala, Albert; Frühwald, Michael C.; Hasle, Henrik; Heuvel-Eibrink, Mary M. van den; Lauten, Melchior Johannes; De Moerloose, Barbara; Smith, Owen P.; Bernig, Toralf; Gruhn, Bernd; et al. (British journal of haematology, 2016)
Low-dose azacitidine is efficient and safe in the therapy of malignant myeloid disorders in adults but data in children are lacking. We present a retrospective analysis of 24 children and young adults with myelodysplastic syndrome (MDS) who received azacitidine at the time of first diagnosis or relapse after allotransplant (2 children were treated with azacitidine both initially and for relapse). Diagnoses were refractory cytopenia of childhood (N = 4), advanced primary MDS (N = 9) and secondary MDS (N = 11). The median duration of treatment was four cycles. Azacitidine was well tolerated, but cytopenias led to dose reduction in five cases. Treatment was discontinued in one child because of impaired renal function. Sixteen MDS patients were treated with azacitidine at first diagnosis. One complete clinical remission was observed and one child showed complete marrow remission; six children experienced stable disease with haematological improvement. Ten children received azacitidine for relapsed MDS after transplant: of these, seven experienced stable disease for 2-30 cycles (median 3), including one patient with haematological improvement for seven cycles. In summary, azacitidine is effective in some children with MDS and appears to be a non-toxic option in palliative situations to prolong survival.